Spin valve sensors for ultrasensitive detection of superparamagnetic nanoparticles for biological applications - Li, Guanxiong; Sun, Shouheng; Wilson, Robert J.; White, Robert L.; Pourmand, Nader; Wang, Shan X. (Sensors and actuators. A. Physical., 2006)
We present giant magnetoresistance (GMR) spin valve sensors designed for detection of superparamagnetic nanoparticles as potential biomolecular labels in magnetic biodetection technology. We discuss the sensor design and experimentally demonstrate that as few as ∼23 monodisperse 16-nm superparamagnetic Fe 3O 4 nanoparticles can be detected by submicron spin valve sensors at room temperature without resorting to lock-in detection. A patterned self-assembly method of nanoparticles, based on a polymer-mediated process and fine lithography, is developed for the detection. It is found that sensor signal increases linearly with the number of nanoparticles.